PEMETAAN ZONASI TINGKAT RISIKO COVID-19 MENGGUNAKAN METODE K-MEANS CLUSTER BERBASIS WEBGIS DI KOTA BOGOR - Andi Irawan; Erwin Hermawan; Freza Riana (Universitas Widyatama, 2022)
Coronaviruses, also known as COVID-19, is a virus that attacks the respiratory system. This virus is growing very rapidly in transmission from human to human. The distribution rate in Indonesia is quite high, one of the areas exposed to COVID-19 is Bogor City. The city of Bogor occupies a moderately dangerous status, where from March 2020 to August 2021 the number of confirmed positive cases was 35,583 cases, while for patients who were confirmed positive recovered reached 35,062 people, and patients who were confirmed positive died as many as 521 people. From data obtained from the Bogor City Health Office, the daily dynamics of the COVID-19 virus continues to show an increase. The COVID-19 zoning distribution map for the Bogor City area at the kelurahan level is still not available. Therefore, this study utilizes a geographic information system (GIS) within the COVID-19 zone by applying the Kmeans Cluster method to cluster the distribution areas of the COVID-19 virus. The grouping is done based on the parameters of the number of positive cases and patients who died. This study produced a COVID-19 zoning map. Based on the test, the definite number of clusters is 3 clusters. Where the zoning division based on the COVID-19 Task Force is divided into red for the high zone, orange for the medium zone, yellow for the low zone, and areas that are not exposed to COVID-19 cases are in the green category or there are no cases. The result of this study is a COVID-19 zoning map that is displayed in WEBGIS form.